Application of three-dimensional computed tomography bronchography and angiography in thoracoscopic anatomical segmentectomy of the right upper lobe: A cohort study - Wang, Mingbo; Lv, Huilai; Wu, Tao; Gao, Wenda; Tian, Yang; Gai, Chunyue; Tian, Ziqiang (Frontiers in Surgery, 2022)
Objective: Three-dimensional computed tomography bronchography and angiography (3D-CTBA) can provide detailed imaging information for pulmonary segmentectomy. This study aimed to investigate the safety and effectiveness of 3D-CTBA guidance of anatomical segmentectomy of the right upper lobe (RUL). Methods: This was a retrospective analysis of anatomical segmentectomy of the RUL at the Thoracic Surgery Department of the Fourth Hospital of Hebei Medical University from December 9, 2013, to June 2, 2021. Preoperatively, all patients underwent contrast-enhanced CT of the chest (to determine the size of the pulmonary nodule) and a lung function test. 3D-CTBA has been performed since 2018; the patients with vs. without 3D-CTBA were compared. Segmentectomy was performed according to nodule location. Results: Of 139 patients (46 males and 93 females, aged 21-81 years), 93 (66.9%) completed single segmentectomy, three (2.2%) completed single subsegmentectomy, 29 had combined subsegmentectomy, seven had segmentectomy combined with subsegmentectomy, and six had combined resection of two segments. Eighty-five (61.2%) patients underwent 3D-CTBA. 3D-CTBA cases had decreased intraoperative blood loss (67.4±17.6 vs. 73.1±11.0, P=0.021) and shorter operation time (143.0±10.8 vs. 133.4±20.9, P=0.001). 3D-CTBA (Beta=-7.594, 95%CI: -12.877~-2.311, P=0.005) and surgical procedure (Beta=9.352, 95%CI: 3.551~-15.153, P=0.002) were independently associated with intraoperative blood loss. 3D-CTBA (Beta=-13.027, 95%CI: -18.632~17.422, P<0.001) and surgical procedure (Beta=7.072, 95%CI: 0.864~13.280, P=0.026) were also independent factors affecting the operation time. Conclusion: Preoperative use of 3D-CTBA to evaluate the pulmonary vessels and bronchial branch patterns of the RUL decreased blood loss and procedure time and so would be expected to improve the safety and effectiveness of thoracoscopic segmentectomy.